2023
DOI: 10.1021/acsomega.2c07018
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Bioactive Polymer Composite Film of PVA/Gelatin/Tannic Acid Downregulates the Pro-inflammatory Cytokines to Expedite Healing of Full-Thickness Wounds

Abstract: Curcumin (Cur) entrapped poly­(vinyl alcohol) (PVA)/gelatin composite films were prepared by cross-linking with tannic acid (TA) as bioactive dressings for rapid wound closure. Films were evaluated for mechanical strength, swelling index, water vapor transmission rate (WVTR), film solubility, and in-vitro drug release studies. SEM revealed uniform and smooth surfaces of blank (PG9) and Cur-loaded composite films (PGC4). PGC4 exhibited excellent mechanical strength (tensile strength (TS) and Young’s modulus (YM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…However, curcumin can inhibit the secretion of proinflammatory cytokines. As shown in Figure D,E, we observed a significant decrease in IL-6 and TNF-α in the Nap-pep@Cur (S3) group, which was consistent with Nida Rashid’s finding that “curcumin-supported poly­(vinyl alcohol)/gelatin/tannic acid bioactive polymers reduce TNF-α and IL-6 levels in vivo at wound sites”. Furthermore, as shown in Figure C, the Cur-release rate of Nap-pep@Cur (S3) reached 66.26% after 24 h in vivo.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, curcumin can inhibit the secretion of proinflammatory cytokines. As shown in Figure D,E, we observed a significant decrease in IL-6 and TNF-α in the Nap-pep@Cur (S3) group, which was consistent with Nida Rashid’s finding that “curcumin-supported poly­(vinyl alcohol)/gelatin/tannic acid bioactive polymers reduce TNF-α and IL-6 levels in vivo at wound sites”. Furthermore, as shown in Figure C, the Cur-release rate of Nap-pep@Cur (S3) reached 66.26% after 24 h in vivo.…”
Section: Resultssupporting
confidence: 90%
“…Imbalance of inflammatory factors may impair fibroblast functions such as proliferation and migration. 51 However, curcumin can inhibit the secretion of proinflammatory cytokines. As shown in Figure 6D,E, we observed a significant decrease in IL-6 and TNF-α in the Nappep@Cur (S3) group, which was consistent with Nida Rashid's finding 52 that "curcumin-supported poly(vinyl alcohol)/gelatin/tannic acid bioactive polymers reduce TNF-α and IL-6 levels in vivo at wound sites".…”
Section: Evaluation Of Wound Healingmentioning
confidence: 99%
“…Dietary polyphenols can decrease arterial stiffness [ 62 ], and it was reported that curcumin downregulates the pro-inflammatory cytokines TNF-α and IL-6 [ 71 ]. Thus, the joint consideration of these two articles allows arriving at the conclusion that ECM de-stiffening downregulates the expression of pro-inflammatory cytokines, and it has recently been reported that matrix stiffness exacerbates the pro-inflammatory responses of vascular smooth muscle cells [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dietary polyphenols can decrease arterial stiffness [62], and it was reported that curcumin downregulates the pro-inflammatory cytokines TNF-α and IL-6 [71]. Thus, the joint consideration of these two articles allows arriving at the conclusion that ECM destiffening downregulates the expression of pro-inflammatory cytokines, and it has recently been reported that matrix stiffness exacerbates the pro-inflammatory responses of vascular smooth muscle cells [72].…”
Section: Polyphenols Decrease Ecm Stiffnessmentioning
confidence: 99%